Clinicians’ prescribing pattern, rate of patients’ medication adherence and its determinants among adult hypertensive patients at Jimma University Medical Center: Prospective cohort study - Bekalu Kebede Simegn (Public Library of Science (PLoS), 2021)
Background Many studies conducted in the past focused on patients’ sociodemographic factors and medical profiles to identify the determinants of suboptimal blood pressure control. However, prescribing patterns and clinicians’ adherence to guidelines are also important factors affecting the rate of blood pressure control. Therefore, this study aimed to determine clinicians’ prescribing patterns, patients’ medication adherence, and its determinants among hypertensive patients at Jimma University Medical Center. Methods A general prospective cohort study was conducted among hypertensive patients who had regular follow-up at Jimma university ambulatory cardiac clinic from March 20, 2018, to June 20, 2018. Patients’ specific data was collected with a face-to-face interview and from their medical charts. Clinicians’ related data were collected through a self-administered questionnaire. Data were analyzed using SPSS version 21.0. Bivariate and multivariable logistic regression analyses were done to identify key independent variables influencing patients’ adherence. P-Values of less than 0.05 were considered statically significant. Results From the total of 416 patients, 237(57.0%) of them were males with a mean age of 56.50 ± 11.96 years. Angiotensin-converting enzyme inhibitors were the most frequently prescribed class of antihypertensives, accounting for 261(63.7%) prescriptions. Combination therapy was used by the majority of patients, with 275 (66.1%) patients receiving two or more antihypertensive drugs. Patients’ medication adherence was 46.6%, while clinicians’ guideline adherence was 44.2%. Patients with merchant occupation (P = 0.020), physical inactivity (P = 0.033), and diabetes mellitus co-morbidity (P = 0.008) were significantly associated with a higher rate of medication non-adherence. Conclusion The rate of medication adherence was poor among hypertensive patients. Physicians were not-adherent to standard treatment guideline. The most commonly prescribed class of drugs were angiotensin-converting enzyme inhibitors. Effective education should be given to patients to improve medication adherence. Prescribers should be trained on treatment guidelines regularly to keep them up-to-date with current trends of hypertension treatment and for better treatment outcomes.